Rancang Bangun Sistem Komunikasi Data Perangkat Virtual Reality Berbasis Modul Komunikasi Wireless Bluetooth Hc-06 - Ramadhan, M Rizki; Cristopher; Ramadhani, Inda Dwi; Sahlendar A, Rheyuniarto; Istiqphara1, Swadexi (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2021)
The occurrence of the Corona virus Disease 19 pandemic or commonly called Covid-19 makes it difficult for humans to carry out sports activities outside the home, thus making humans more susceptible to contracting the Covid-19 virus due to a lack of physical fitness which lowers human immunity. This requires a tool that can support sports activities that do not require humans to leave the house to do sports activities. The virtual reality system for sports was created to overcome the difficult needs of human sports during a pandemic, by utilizing the bluetooth transmission system as the main controlerl of the virtual reality system. The research method uses the waterfall method where the work is carried out linearly or in succession. The use of the CRC method as a method of checking data transmission so that no error data is sent is intended to minimize the decline in the performance of the virtual reality system used by users